AN ANALYSIS OF THE STATUS QUO OF CHINA’S AID TO PACIFIC ISLAND COUNTRIES: Received: 19th April 2021; Revised: 10th July 2021, 5th November 2021, 5th January 2022; Accepted: 7th January 2022 - Fan, Xuande; Gu, Yuting (PEOPLE: International Journal of Social Sciences, 2022)
In recent years, with the increase of China’s aid to Pacific Island Countries（PIC), the issue of China’s aid to Pacific Island countries has become a research hotspot in academic circles, and scholars from various countries have conducted different degrees of research on this. This article is a review article, enumerating some major books and articles for research on this issue. To better understand the research status of scholars from various countries in recent years on this issue, this article uses the literature analysis method to summarize and briefly analyze the main research results of the academic community. After sorting it out, it is found that scholars have different attitudes towards China’s aid to Pacific Island countries. Some scholars hold negative views of China’s aid, while China’s scholars appreciate their aid. Regarding the development trend of this issue, scholars gradually gained a more comprehensive and detailed understanding of China’s aid in the region and began to conduct more case studies. This research review can help people quickly understand the current research status of this issue. The article collates scholars’ analysis of various aspects of China’s aid, such as purpose, impact, and limitations.